العوامل المؤثرة على استخدام التأجير التمويلي بالمصارف التجارية " دراسة ميدانية عن المصارف التجارية الليبية العاملة في المنطقة الساحل الغربي" (Comprehensive Journal of Science, 2026)
This study aimed to identify financial leasing, explain the regulations and legislation governing the financial leasing system, the guarantees obtained, and its importance. It also aimed to identify the factors influencing the use of financial leasing in commercial banks operating on the West Coast. The researchers adopted a descriptive-analytical approach, using a questionnaire as a data collection tool. (40) questionnaires were prepared and (32) were returned and distributed to employees of commercial banks. The study data was analyzed and the levels of the study variables were evaluated using statistical analysis tools. The study reached a number of conclusions, the most important of which is: There are no factors influencing the use of financial leasing in commercial banks. One of the most important recommendations of the study is: Financial leasing is characterized by flexibility; therefore, officials should include financial leasing options in commercial banks to create opportunities for investing funds. Keywords: Financial leasing, commercial banks, Islamic finance, laws and legislation